2016
DOI: 10.1002/2015wr017797
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal evolution of water storage changes in India from the updated GRACE‐derived gravity records

Abstract: Investigating changes in terrestrial water storage (TWS) is important for understanding response of the hydrological cycle to recent climate variability worldwide. This is particularly critical in India where the current economic development and food security greatly depend on its water resources. We use 129 monthly gravity solutions from NASA's Gravity Recovery and Climate Experiment (GRACE) satellites for the period of January 2003 to May 2014 to characterize spatiotemporal variations of TWS and groundwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 66 publications
6
83
0
1
Order By: Relevance
“…3c. In addition, Panda and Wahr 43 reported during 2012 year that the GRACE-derived negative water storage anomaly for the post monsoon and monsoon were less compared to previous years. In addition to that post monsoon of 2012 (October to December) and pre monsoon (January to May) of 2013 having a consistent temporal behaviour of groundwater level anomaly was noticed by in situ data for the years 2011 and 2012.…”
Section: Technical Validationmentioning
confidence: 99%
“…3c. In addition, Panda and Wahr 43 reported during 2012 year that the GRACE-derived negative water storage anomaly for the post monsoon and monsoon were less compared to previous years. In addition to that post monsoon of 2012 (October to December) and pre monsoon (January to May) of 2013 having a consistent temporal behaviour of groundwater level anomaly was noticed by in situ data for the years 2011 and 2012.…”
Section: Technical Validationmentioning
confidence: 99%
“…Severe drought reduced TWS and caused food shortages in Madagascar, Mozambique, Zimbabwe, and neighboring countries. A region centered on Nepal was similarly afflicted, although continuing groundwater withdrawals for irrigation in northern India (Rodell et al 2009;Panda and Wahr 2016) contributed to the observed signal. TWS also decreased in Mexico and northwest Australia.…”
mentioning
confidence: 97%
“…It has been reported that climate change exacerbates the already reduced natural streamflow due to dams and water withdrawals in most parts of the country (Döll et al 2012). The recent acute groundwater depletion in the Indo-gangetic plains primarily due to irrigation water withdrawals was also found to be influenced by the marked rise in temperature since 2008 (Panda and Wahr 2016). The increase in water demands and reduced water availability due to climate change is projected to decrease the area under irrigation substantially by 2030 (Taheripour et al 2015).…”
Section: Linkages To Water Resources In the Elwc Nexusmentioning
confidence: 87%